Clinical dilemmas in diabetes - Vella, Adrian; Rizza, Robert (Chichester, West Sussex, UK : Wiley-Blackwell Publishing, 2011)
"Clinical Dilemmas in Diabetes provides evidence-based clinical guidance on the most common and problematic areas of concern encountered by health professionals when diagnosing, treating, and managing patients with diabetes. Topics reflect current interest, specific recent developments, and areas of controversy. Each brief chapter opens with a learning points box to aid easy assimilation of the main issues. Contributors are international and well known diabetes specialists, thus providing a global perspective, writing under the editorial guidance of two Mayo Clinic experts, Professor Adrian Vella and a former president of the American Diabetes Association, Professor Robert Rizza"--Provided by publisher.
Machine generated contents note: Part 1. Pre-Diabetes and the Diagnosis of Diabetes. -- 1. Is Pre-Diabetes a Risk Factor or is it a Disease? (Kalpana Muthusamy and Adrian Vella). -- 2. Early Diagnosis of Type 1 Diabetes - Useful or a Phyrrhic Victory? (Chiara Guglielmi and Paolo Pozzilli). -- 3. How Should Secondary Causes of Diabetes be Excluded? (Aonghus O'Loughlin and Sean F. Dinneen). -- 4. Screening Patients with Prediabetes and Diabetes for Cardiovascular Disease (Deepika S. Reddy and Vivian Fonseca). -- Part 2. Initial Evaluation and Management of Diabetes. -- 5. What is the Role of Self-Monitoring in Diabetes? Is there a Role for Postprandial Glucose Monitoring? How Does Continuous Glucose Monitoring Integrate into Clinical Practice? (Rami Almokayyad and Robert Cuddihy). -- 6. The Optimal Diet for Diabetes is? (Maria L. Collazo-Clavell). -- 7. How to Determine When to Pursue Lifestyle vs. Pharmacotherapy at Diagnosis? (Galina Smushkin and F John Service). -- 8. Insulin Sensitizers vs. Secretagogues as First Line Therapy for Diabetes: Rationale for Clinical Choice (Robert J. Richards, L. Yvonne Melendez-Ramirez and William T. Cefalu). -- 9. Are Insulin Sensitizers Useful Additions to Insulin Therapy? (John W. Richard III and Philip Raskin). -- 10. Is There a Role for Incretin-Based Therapy in Combination with Insulin? (Matheni Sathananthan and Adrian Vella). -- 11. HbA1c: Is it the Most Important Therapeutic Target in Outpatient Management of Diabetes? (Steven A. Smith). -- Part 3. Management of Associated Risk Factors and Disease. -- 12. Primary Therapy for Obesity as the Treatment of Type 2 Diabetes (Manpreet Mundi and Michael D. Jensen). -- 13. Are Statins the Optimal Therapy for Cardiovascular Risk in Patients with Diabetes? Are Triglycerides an Important Independent Risk Factor for Diabetes? (Michael O'Reilly and Timothy O'Brien). -- 14. The Role of Bariatric Surgery in Obese Patients with Diabetes: Primary or Rescue Therapy? (Praveena Gandikota and Blandine Laferrère). -- 15. To what extent should hyperglycemia be avoided in Critical Illness and the Postoperative Period? (Kalpana Muthusamy and John M. Miles). -- 16. Is There an Optimal Revascularization Strategy in Diabetic Patients with Ischemic Heart Disease? (Stephen H. McKellar, Morgan L. Brown and Robert L. Frye).
Includes bibliographical references and index.
Keywords: Diabetes Mellitus -- therapy; Diabetes Mellitus -- diagnosis; Evidence-Based Medicine -- methods